2013
DOI: 10.1016/j.respol.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Bridges or isolates? Investigating the social networks of academic inventors

Abstract: We analyze the acquaintances of a sample of academic inventors and their paired controls to investigate the contribution of social networks to the generation of inventive ideas in academe. Prior to patenting, inventors work in networks of similar dimension and structure as those of their colleagues who do not invent. The ego-networks of the inventors are however more cohesive (denser), a circumstance that is often seen as associated to the exchange of more fine-grained information and to a greater climate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…1). More specifically, our results complement the findings by Forti et al (2013) who found no evidence that after patenting the scientists isolate or close their networks and whereby scientists' networks are mapped and measured on the basis of their co-publication activity.…”
Section: Beyond a Selection Effect -Scientific Footprint Based On H-isupporting
confidence: 89%
See 1 more Smart Citation
“…1). More specifically, our results complement the findings by Forti et al (2013) who found no evidence that after patenting the scientists isolate or close their networks and whereby scientists' networks are mapped and measured on the basis of their co-publication activity.…”
Section: Beyond a Selection Effect -Scientific Footprint Based On H-isupporting
confidence: 89%
“…At the same time, a majority of reported empirical findings report a positive relationship between patenting and publication outcomes of academic researchers (e.g. Fabrizio and Di Minin, 2008;Van Looy et al, 2006;Breschi et al, 2007;Czarnitzki et al, 2007;Stephan et al, 2007;Larsen, 2011;Forti et al, 2013). Patents as commercialized discoveries seem to be derivatives of scientific work rather than substitutes (Murray, 2006).…”
Section: The Entrepreneurial University Phenomenonmentioning
confidence: 99%
“…In doing so, they limit both the need for permanent as well as temporary geographical proximity between their supervisors (see proposition 4 in Section 4.4). This brokerage role for PhD students is one that is not much considered in the literature to date, as studies of brokerage in academic networks point mostly at roles for senior academics who manoeuvred gradually into a brokerage position in the network through patenting and publishing (Forti, Franzoni, and Sobrero 2013;Lissoni 2010). These typical brokerage roles are held by academics in what could be considered 'strategic positions' in the overall network.…”
Section: Discussion: Face-to-face Contacts Still Important In the Eramentioning
confidence: 99%
“…Forti et al (2013) find that inventors' networks are larger, more connected and more complex than those of their colleagues who never filed a patent, consistently with Meyer (2006). Agrawal and Henderson (2002) argue that researchers who patent extensively may be more highly cited by industry.…”
Section: Academic Patenting and Scientific Impactmentioning
confidence: 52%